Long-Chain Fatty Acids Degradation by Desulfomonile Species and Proposal of “Candidatus Desulfomonile Palmitatoxidans” - Alves, Joana I.; Salvador, Andreia F.; Castro, A. Rita; Zheng, Ying; Nijsse, Bart; Atashgahi, Siavash; Sousa, Diana Z.; Stams, Alfons J. M.; Alves, M. Madalena; Cavaleiro, Ana J. (Frontiers in Microbiology, 2020)
Microbial communities with the ability to convert long-chain fatty acids (LCFA) coupled to sulfate reduction can be important in the removal of these compounds from wastewater. In this work, an enrichment culture, able to oxidize the long-chain fatty acid palmitate (C16:0) coupled to sulfate reduction, was obtained from anaerobic granular sludge. Microscopic analysis of this culture, designated HP culture, revealed that it was mainly composed of one morphotype with a typical collar-like cell wall invagination, a distinct morphological feature of the Desulfomonile genus. 16S rRNA gene amplicon and metagenome-assembled genome (MAG) indeed confirmed that the abundant phylotype in HP culture belong to Desulfomonile genus (ca. 92 % 16S rRNA gene sequences closely related to Desulfomonile spp.; and ca. 82 % whole genome shotgun (WGS)). Based on similar cell morphology and average nucleotide identity (ANI, 77 %) between the Desulfomonile sp. in HP culture and the type strain D. tiedjei DCB-1T, we propose a novel species designated as “Candidatus Desulfomonile palmitatoxidans”. This bacterium shares 94.3 % and 93.6 % 16S rRNA gene identity with D. limimaris DCB-MT and D. tiedjei DCB-1T, respectively. Based on sequence abundance of Desulfomonile-morphotype in HP culture, its predominance in the microscopic observations, and presence of several genes coding for enzymes involved in LCFA degradation, the proposed species “Ca. Desulfomonile palmitatoxidans” most probably plays an important role in palmitate degradation in HP culture. Analysis of the growth of HP culture and D. tiedjei strain DCB-1T with short- (butyrate), medium- (caprylate) and long-chain fatty acids (palmitate, stearate and oleate) showed that both cultures degraded all fatty acids coupled to sulfate reduction, except oleate that was only utilized by HP culture. In the absence of sulfate, neither HP culture, nor D. tiedjei strain DCB-1T degraded palmitate when incubated with Methanobacterium formicicum as a possible methanogenic syntrophic partner. Unlike D. tiedjei strain DCB-1T, “Ca. Desulfomonile palmitatoxidans” lacks reductive dehalogenase genes in its genome, and HP culture was not able to grow by organohalide respiration. An emended description of the genus Desulfomonile is proposed. Our study reveals an unrecognized LCFA degradation feature of the Desulfomonile genus.